Development of a Creative Problem-Solving test-based Higher Order Thinking Skills: A Rasch Model Measurement - Farida, Farida; Alamsyah, Yosep Aspat; Suherman, Suherman (JKPM (Jurnal Kajian Pendidikan Matematika), 2025)
Creative Problem Solving (CPS) is increasingly valued in independent curriculum education, yet the comprehensive psychometric validation of CPS assessment tools remains limited. This study aimed to develop and validate an instrument to measure CPS skills among students using the Rasch model. A total of 137 higher education students participated. Analysis showed the assessment items fit the Rasch Model well, with strong item-person alignment, effective discrimination among difficulty levels, and good reliability. The Wright map revealed clear patterns between item difficulty and student ability. One item showed Differential Item Functioning (DIF) favouring male students. Furthermore, fourth-semester female students outperformed those in later semesters. Significant differences in CPS ability were found between gender and between urban and rural students, emphasising the need for targeted differentiation strategies in education. These findings underscore the importance of using validated and inclusive assessments to inform equitable teaching practices and curriculum design that support diverse learners in developing CPS skills.